Sharia-Based 7P Strategy and the Challenge of Asymmetric Digitalization in Building Millennial Saving Interest (A Case Study at BMT NU Genteng) - Muhamad Fajar Bayu Pratama; Muhammad Kanzul Fikri (STAI AN-NAJAH INDONESIA MANDIRI, 2025)
This study aims to analyze the implementation of the 7P marketing strategy and the saving interest of the millennial generation at BMT NU Genteng through a qualitative case study approach. Using a case study design, data were collected through in-depth interviews, observation, and document analysis. Data analysis was conducted using SWOT analysis. The results show that the Sharia-based 7P strategy is effective in building saving interest by positioning products as financial and educational benefit packages and utilizing digital promotion. However, asymmetric digitalization was found, where digital progress is concentrated only in promotion, while service processes remain manual. The strategy influences saving interest through a tiered mechanism from awareness to action, with Islamic values playing a dual role as both spiritual fulfillment and identity markers. The study concludes that an integrated 7P strategy, supported by competent human resources and comprehensive digital transformation, is crucial for developing the multidimensional saving interest of millennials. Key recommendations include developing an integrated digital roadmap and enhancing continuous human resource capacity building..